New Opioid Analgesic Approvals and Outpatient Utilization of Opioid Analgesics in the United States, 1997 through 2015. (May 2018) - Chai, Grace; Xu, Jing; Osterhout, James; Liberatore, Mark A.; Miller, Kathleen L.; Wolff, Carolyn; Cruz, Marisa; Lurie, Peter; Dal Pan, Gerald
Abstract : Background: The opioid epidemic, driven in part by increased prescribing, is a public health emergency. This study examines dispensed prescription patterns and approvals of new opioid analgesic products to investigate whether the introduction of these new drugs increases prescribing. Methods: Prescribing patterns based on dispensed prescription claims from the U.S. retail setting were assessed with new brand and generic opioid analgesic products approved in the United States from 1997 through 2015. Results: From 1997 through 2015, the U.S. Food and Drug Administration (Silver Spring, Maryland) approved 263 opioid analgesic products, including 33 brand products. Dispensed prescriptions initially increased 80% from 145 million prescriptions in 1997 to a peak of 260 million prescriptions in 2012 before decreasing by 12% to 228 million prescriptions in 2015. Morphine milligram equivalents dispensed per prescription increased from 486 in 1997 to a peak of 950 in 2010, before decreasing to 905 in 2015. In 2015, generic products accounted for 96% (218/228 million prescriptions) of all opioid analgesic prescriptions dispensed. The remaining prescriptions were dispensed for brand products, of which nearly half were dispensed for one brand product (OxyContin, Purdue, USA). Conclusions: There has been a dramatic increase in prescriptions dispensed for opioid analgesics since 1997 and an increasing number of opioid analgesic approvals; however, the number of prescriptions dispensed has declined since 2012 despite an increasing number of approvals. Examination of dispensed prescriptions shows a shifting and complex market where multiple factors likely influence prescribing; the approval of new products alone may not be sufficient to be a primary driver of increased prescribing. Visual Abstract: An online visual overview is available for this article athttp://links.lww.com/ALN/B705 . Abstract : Data on new brand and generic opioid analgesic product approvals, and on retail dispensed prescription claims, were used to evaluate the opioid product space. Opioid prescriptions dispensed and amount per prescription nearly doubled, and total morphine milligram equivalents more than tripled, from 1997 to the peak in 2010, and partially declined thereafter. Generic products accounted for 68% of total opioid prescriptions in 1997 and 96% in 2015. Approval of new branded opioid products alone does not appear to be a primary driver of increased opioid prescribing.